PERBEDAAN PENGETAHUAN DAN SIKAP PASIEN DIABETES MELLITUS RAWAT INAP RUMAH SAKIT ISLAM SAMARINDA SEBELUM DAN SESUDAH KONSELING GIZI DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL - Siswanto Siswanto; Ismail Kamba; Siti Aminah (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Diabetes mellitus is one of the communicable diseases that have become a public health problem, not only in Indonesia but also the world. Currently morbidity of diabetes mellitus is increasing every year, where in 2006 there were 14 million people in 2011 and ranks fourth with 773 cases. DM is also a cause of disease mortality by 5.8%. And Samarinda own particular Islamic Hospital years 2009, there were 449 patients with DM, and 2011 an increase in the 1931 patients with diabetes mellitus. To increase patients’ knowledge about diabetes and diabetic patients be directing attitudes that support or positive attitude towards keeping blood glucose levels to remain normal. Methode to use pra eksperiment with one group pretest posttest. individual conseling withAudiovisual media. There is increased knowledge about diabetes diabetic patients before and after intervention with increasing value of 3.77 (p value = 0.000) and increase in attitudes regarding diabetes mellitus diabetic patients with an increase in the value of 5,35 (p value = 0.003). There was an increase in knowledge and attitudes of patients hospitalized with diabetes mellitus hospital after islam samarinda given nutritional counseling using audio-visual media